(untitled) (International Journal of Engineering and Computer Science, 2015)
Module integrated converters (MICs) have been un- der rapid development for single-phase grid-tied photovoltaic ap- plications. The capacitive energy storage implementation for the double-line-frequency power variation represents a differentiat- ing factor among existing designs. This paper introduces a newtopology that places the energy storage block in a series-connected path with the line interface block. This design provides inde- pendent control over the capacitor voltage, soft-switching for all semiconductor devices, and the full four-quadrant operation with the grid. The proposed approach is analyzed and experimentally demonstrated.